Evaluating the Acceptance of Wordwall as a Multimodal Learning Media Using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) - Oktaviani, Windi Nur; Abidin, Yunus; Kurniawan, Dede Trie (LPPM Institut Pendidikan Nusantara Global, 2025)
Teachers require learning media to implement education. With the progress in technology, educators must possess the ability to utilize technology-driven learning tools in education. This research aims to identify the factors that affect the acceptance of wordwall multimodal learning models among elementary school teachers, utilizing the Unified Theory of Acceptance and Use of Technology 2(UTAUT2) framework. The approach employed in this research is a quantitative method utilizing a survey approach with a questionnaire. Data analysis was performed utilizing the PLS-SEM methodology. The study data was collected by distributing surveys to 105 elementary school educators. The findings of this study suggest that the variables affecting teacher acceptance of wordwall multimodal learning tools include behavioral intention, usage behavior, performance expectations, effort expectations, social influences, facilitating conditions, hedonic motivation, price values, and established habits. Considering the R Square value, this online multimodal learning model is effective for implementation in elementary school education.